Urban Flooding Model SWMM Parameter Sensitivity Analysis under Different Catchment Areas - HE Peiying; ZHENG Yanhui; HE Yanhu (Renmin Zhujiang)
Parameter sensitivity analysis is an important step in determining the main parameters of a model. Taking two regions with different catchment areas in Guangzhou as the research objects, the Monte Carlo Sobol index method was used to analyze the parameter sensitivity of different results (total runoff, peak flow, peak time) with different catchment areas. The results show that with different catchment areas, the main sensitive parameters affecting different output results of the model are different. ① The main sensitive parameters affecting the total runoff output of the model are the basic characteristic parameters of the catchment area. But when the catchment areas are different, the sensitive parameters to be considered are slightly different. The research area with a larger catchment area needs to consider infiltration parameter, and the research area with a smaller catchment area needs to consider Manning roughness parameters. ②The main sensitive parameters affecting peak flow and peak time output are the characteristic parameters of the catchment area and the Manning roughness coefficient. But when the catchment areas are different, the sensitive parameters that are first considered are slightly different. The research area with a larger catchment area mainly considers the characteristic parameters of the catchment area, and the research area with a smaller catchment area mainly considers Manning roughness parameters. This study can provide reference significance for the main parameters determining in modeling similar regions in cities in the future and improve simulation accuracy and modeling efficiency.